The Lithuanian Forest Sector Towards the 21st Century: the Strategic Problems of the Transitional Period - Gaižutis, Algis (Ekonomika, 1997)
Strategy specifies the direction. Long-term strategy usually means the ability to answer the following questions: • Where are we now? • Where do we want to go? • How do we get there? Changes in the economical, demographic and political development of the country, the value orientation of the Government expressed by the Forest Policy, the availability of resources, the demand-supply situation in the markets, and the past and present performance of business all greatly affect the formulation of Forest Sector Strategies for the future. This paper examines the first two questions presented above. Firstly, we shall introduce ourselves shortly to the present situation in which the Lithuanian Forest Sector exists. Secondly, we shall look at future possibilities. The important changes of the operating environment of the transitional period in the whole economy of Lithuania are also discussed.